079 "MitraClip, a summit well worth reaching for". Outcome of transcatheter mitral valve clip for the management of mitral regurgitation in high risk group patients unsuitable for surgical intervention. (16th May 2012) - Keshavarzi, F; Hoye, A; Clark, A L; Oliver, R; Cleland, J G; Alamgir, F
Abstract : Introduction: Mitral regurgitation (MR) can cause or complicate heart failure, affecting patient quality of life and survival. Surgical mitral valve (MV) repair or replacement is effective but associated with substantial morbidity and mortality in high-risk groups. MV clipping is a potential alternative, minimally invasive and lower risk procedure that has been shown to have similar benefits to surgical repair in randomised trials. The aim of this study was to assess the impact of the MitraClip procedure on MR and functional class in clinical practice in patients who were refused MV surgery. Method: Patient demographics including age, gender, cardiac / valve structure and function, aetiology of MR, duration of the procedure, complications, duration of hospital stay and the NYHA class pre and post procedure were recorded. SPSS statistical tool was used to analyse the data. Results: 30 patients unsuitable for surgery were referred to our centre. Twelve patients were excluded because of co-morbidities and were considered clinically inappropriate MitraClip (n=5; 42%) and/or because of unsuitable valve morphology (n=7; 58%). Of 18 patients who underwent the procedure, the mean age was 73 (range 58–85) years and 14 were men. MR was functional in 15 (83%), due to valve prolapse in 2 and degenerative valve disease in one. Two clips were deployed in four patients. The median procedure time was 227 min (123–380 min). Procedures longer than 2 h involved multiple clip application as well as coronary angioplasty. Mean hospital stay was 6 days (1–18 days) and 78% of patients were discharged within 1 week. Complications included failure to remove the catheter after the MitraClip application in one patient with severe pre-existing heart failure who later died of heart failure, bleeding from the groin and septicaemia. One patient who had been hospitalised for 5 months with severe heart failure died from pericardial tamponade most likely due to atrial wall damage. Among surviving patients, MR severity improved to grade I/II in 84%, to grade III in 16%. Of patients initially in NYHA IV, one died, one improved to NYHA I, one to NYHA III and one did not improve. Of 14 patients initially in NYHA III, Nine (62%) improved to NYHA I/II, one died and four did not improve substantially. Conclusion: In high-risk patients who have been declined mitral valve surgery, MV repair using the MitraClip procedure can be done with a moderate risk and with a high procedural success rate. Advances in expertise and technology will improve efficacy and patient safety.